PENINGKATAN KUALITAS TENAGA PENDIDIK MELALUI PUBLIKASI KARYA ILMIAH BEREPUTASI INTERNASIONAL - Abdul Halim Hasugian (UIN Sumatera Utara Medan, 2019)
His research is a field study that is kaulitatif in which the data and information are obtained and collected through direct studies of improving the quality of teaching staff through internationally reputed scientific work carried out in the science and technology faculty of the Sumatra State Islamic University of Medan (UINSU). Techniques used in data collection is done by observation, interviews and documentation. The results of the research found by researchers in the field are that there are still educators who have never published scientific work with international or national reputation. To improve the quality of teaching staff, one of the trainings was provided by researchers to help motivate them to write scientific works. . In the training to improve the quality of educators of internationally reputed scientific works, present speakers or experts who are well aware of scientific work. This research also proves that the competence of the teaching staff in improving the quality of scientific work is very low and has not taken significant results. One way to improve the quality of experts in the publication of internationally reputed scientific work, namely by the existence of workshops on scientific writing must be consistent in the writing of scientific works both internationally and nationally.